Isolation and cloning of an inulinase gene from an endophytic bacteria - Ali, Abd Manaf; -, Basran; -, N.F.a; -, Mustafa (2010)
In this study, an endophytic bacterium was isolated from Black Solenosternon scutellarioides plant and was named as AS. A simple and rapid method is described for the detection of inulinase-producing bacterial endophyte on agar plate using Remazol Brilliant Blue-inufin as substrate. The inulinase activity of AS bacteria isolate was detected by clear zone surroundings the colonies. The inulinase gene obtained from AS bacterium was amplified by the polymerase chain reaction. Degenerate primers were used specifically designed to pick up the inulinase gene. pGEM-T Easy and E. coli JM109 were used as cloning vector and host strain. respectively. The results showed that the partial sequence of inulinase gene consisted of 449bp. From the comparison with partial amino acid sequence of inulinase. the deduced polypeptide showed high sequence similarity to Paenibaccillus polymyxa and Geobacillus stearothermophilus exo-inulinases.